البصمة التفسيرية الجزائرية عند أعلام الإباضية -الإمام المصعبي وابن بيحمان أنموذجين- (El-Wahat Journal for Research and Studies, 2023)
ملخص:تطرق المقال إلى البصمة التفسيرية عند أعلام الحاضرة الإباضية، محاولا بيان إسهاماتهم وجهودهم في الدرس التفسيري الجزائري وطريقة التعامل مع الآي الكريم، جاء التمثيل بتراث عَلمين اثنين من أكابر أعلام المذهب، وهما: الإمام المصعبي أبو يعقوب، والإمام إبراهيم بن بيحمان، معتمدا على مجموعة من أعمالهم التفسيرية التي لازالت مخطوطة حسب بحثي، وقد أبانت الدراسة عن جهود كبيرة وطريقة فريدة في محاولة استنطاق القرآن الكريم وتفسيره وتأويله بالأدوات والأساليب المتفق عليها عند غالب الفرق الإسلامية، مع إظهار لملمحين بارزين، تمثل الأول في الذب عن أساسيات ومرتكزات المذهب، والثاني في الاستخدام والاستعانة بتأصيلات وتفريعات باقي المذاهب والاتجاهات الفقهية وحتى العقدية المخالفة. كل ذلك في سبيل حسن التوظيف للمناهج والأدوات حتى يخرج الكلام في تفسير مراد الله تعالى صائبا سديدا، قدر الاستطاعة المنوطة.كلمات دالة: المصعبي، بن بيحمان، البصمة، التفسيرية، الإباضية.   Abstract: The article touched on the explanatory footprint when informing the Ibadi metropolis, trying to explain their contributions and their efforts in the Algerian explanatory lesson and how to deal with the noble verse, the representation came with the heritage of two of the most prominent flags of the sect, namely: Imam al-Masabi Abu Ya'qub and Imam Ibrahim ibn bin Bayhman, relying on a collection of their interpretative works that are still manuscript the study showed great efforts and a unique way of trying to interrogate, interpret and interpret the Holy Quran with the tools and methods agreed upon by most Islamic groups, With a manifestation of outstanding hints, the first was to deflect from the fundamentals and foundations of the doctrine, The second is the use and use of the origins and branches of other doctrines and doctrinal and even doctrinal trends. All of this is in order to make good use of the methods and tools so that the explanation of God's purpose will come out as correct as possible. Key words: Al-Masabi, Ben Behman, efforts, interpretive, Ibadi